Low-cost virtual instrumentation of PV panel characteristics using Excel and Arduino in comparison with traditional instrumentation - Aboubakr El Hammoumi; Saad Motahhir; Abdelilah Chalh; Abdelaziz El Ghzizal; Aziz Derouich (Renewables: Wind, Water, and Solar, 2018)
Abstract This paper presents a low-cost solution of virtual instrumentation to provide a new technique for real-time instrumentation of the PV panel characteristics such as voltage, current and power. The system design is based on a low-cost Arduino acquisition board. The acquisition is made through a low-cost current and voltage sensors, and data are presented in Excel by using the PLX-DAQ data acquisition Excel Macro, which allows communication between the ATMega328 microcontroller of an Arduino UNO board and the computer by UART bus. Hence, the I–V and P–V characteristics, which processed under real-time conditions, can be obtained directly and plotted on an Excel spreadsheet without needing to reprogram the microcontroller. A comparison between this low-cost virtual instrumentation and the traditional instrumentation is drawn in this work. It is found that our solution presents several benefits compared to the traditional solution such as the data can be presented in graphical form in real time. Thus, several experimental tests to confirm the effectiveness of the developed virtual instrumentation system are presented in this study.